Shallow soil moisture – ground thaw interactions and controls – Part 1: Spatiotemporal patterns and correlations over a subarctic landscape - X. J. Guan; C. J. Westbrook; C. Spence (Hydrology and Earth System Sciences, 2010)
Soil moisture and ground thaw state are both indicative of a hillslope's ability to transfer water. In cold regions, in particular, it is widely known that the depth of the active layer and wetness of surface soils are important for runoff generation, but the diversity of interactions between ground thaw and surface soil moisture themselves has not been studied. To fill this knowledge gap, detailed shallow soil moisture and thaw depth surveys were conducted along systematic grids at the Baker Creek Basin, Northwest Territories. Multiple hillslopes were studied to determine how the interactions differed along a spectrum of topological, typological and topographic situations across the landscape. Overall results did not show a simple link between soil moisture and ground thaw as was expected. Instead, correlation was a function of wetness. The interaction between soil moisture and ground thaw was more dependent at wetter sites. This indicates that interactive soil moisture and thaw depth behaviour on hillslopes in cold regions changes with location and cannot necessarily be lumped together in hydrological models. To explore further why these differences arise, a companion paper (Guan et al., 2010) will examine how the hydrological and energy fluxes influenced the patterns of moisture and thaw among the study sites.